Effects of herbal supplements in medicine - Dasgupta, Amitava, 1958- (Walter de Gruyter, 2011)
Herbal supplements are available without prescription in many countries throughout the world. Contrary to the popular belief that herbal remedies are safe and effective, many herbal supplements have known toxicity and can interact with many Western drugs causing increased clearance of such drugs and hence treatment failure. This monograph would provide information on how herbal supplements affect laboratory test results thus patient's safety. It is a comprehensive and concise guide for laboratory professionals, physicians and other health care professionals. --Book Jacket.
Keywords: Materia medica, Vegetable.; Clinical chemistry.; Dietary supplements -- Side effects.; elektronické knihy; electronic books